Dampak Penyebaran Virus Corona (Covid 19) terhadap Pemberdayaan UMKM di Kabupaten Sukoharjo - Ika Swasti Putri; Yuniatin Trisnawati DKW (Global Financial Accounting Journal, 2020)
The existence of COVID-19 as a pandemic around the world resulted in the economic road becoming disturbed, especially in the field of SMES. The current impact is the disruption of the economic process in the MSME sector. In addition, the disruption of health and restriction for the economy outside the region also become the impact that the population of the SME community. However, there is a positive impact that can be gained, which is the more creative of SMES actors to get around the current situation with a growing creativity. The government is also anticipating how to keep the SME actors who want to remain in the middle of pandemic so that the synergy between SMES and government is well established.